Conspirators, Conventurers , and the Exception Swallowing the Hearsay Rule - Trachtenberg, Ben (2010)
In recent years, prosecutors-sometimes with the blessing of courts-have argued that when proving the existence of a conspiracy to justify admission of evidence under the Coconspirator Exception to the Hearsay Rule, they need show only that the declarant and the defendant were coventurers with a common purpose, not coconspirators with an illegal purpose. Indeed, government briefs and court decisions specifically disclaim the need to show any wrongful goal whatsoever. This Article contends that such a reading of the Exception is mistaken and undesirable. Conducted for this Article, a survey of thousands of court decisions, including the earliest English and American cases concerning the Exception as well as approximately 2500 federal court opinions discussing the Exception since its federal codification in 1975, makes clear that a conspiracy under the Exception must involve wrongful acts. First, courts and commentators have for centuries described the Exception as concerning illegal or illicit conduct. Second, because the drafters of the Federal Rules of Evidence (and analogous state codes) intended to adopt the common law understanding of the Exception when codifying it in Rule 80I(d) (2) (E), encroachment beyond the historical boundaries of the Exception violates existing rules of evidence. Third, such revisionism could also violate the Confrontation Clause of the Sixth Amendment, which has been interpreted to prohibit admission of testimonial hearsay in criminal trials. To adhere to the historical definition of the Coconspirator Exception to the Hearsay Rule, prosecutors should stop arguing that the conspiracy joined by the declarant and defendant may include purely lawful conduct, and courts encountering such arguments should reject them, lest they find themselves conducting new trials after the rights of convicted defendants find vindication on appeal. Civil litigants should also resist the revisionist interpretation of the Exception, which threatens immense and unnecessary discovery burdens